From Learning to Publication : Training and Assistance in Scientific Writing and Mendeley Maximization for SMPN 1 Bungoro Teachers - Nurhayati; Munira Hasjim; St. Nursa’adah; Indarwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
School teachers need scientific papers in proposing their promotion. However, in general, teachers are still constrained by their ability to write scientific papers. They still do not understand in writing scientific papers. Therefore, they need help to get out of the problem. The Research and Community Service Institute of Hasanuddin University held training and assistance in writing scientific papers and maximizing the use of Mendeley for teachers of SMP Negeri 1 Bungoro Pangkep Regency with the aim of 1) increasing the motivation of teachers of SMP Negeri 1 Bungoro Pangkep in writing scientific papers, 2) SMP Negeri 1 Bunggoro teachers can write scientific articles. The method used is training with lecture and question and answer methods. As for assistance, the discussion method is used through the zoom application. The results of the research show that 1) teachers are motivated to write scientific papers and 2) teachers are encouraged to write scientific papers as evidenced by the number of entries in their research.